Budżet zadaniowy jako instrument formalizacji procesu zarządzania ryzykiem w sektorze publicznym - Tomaszewski, Marek (Activity-Based Budgeting as an Instrument for Formalizing Risk Management Processes in the Public Sector, 2009)
Introduction of activity-based budgeting in the public sector, backed up by appropriate information technology tools, will play a key role in facilitating risk management processes. This is made possible owing to integration of budget-planning, accounting, and task achievement measurement and control systems into one coherent structure. The aim of risk management is to increase the probability of achieving goals. Local government entities that do not run activity-based budgets, do not comply with the standards in this respect. Without specified goals and tasks, measurable indicators of responsibility centres, and the resources necessary in order to achieve the goals set (both material and personal), task monitoring cannot be performed
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 339-348